Mediating relationship of financial practice between financial knowledge and business success: an empirical study on Malaysian small business - Abdullah, Moha Asri; Azam, S. M. Ferdous (2015)
Purpose – The business world metaphorically has turned flat for the onslaught of globalization. The ultimate purpose for achieving business success is a common anticipation for all types of businesses, particularly small businesses that are thought as a nucleus of the business world. The purpose of this research is to assess the mediating relationship of financial practice between financial knowledge and business success of small business in Malaysia. Design/methodology/approach – The research method of this study is survey method, where the unit of analysis is the individual respondent consisting business owners and managers. A sample of 302 data is considered as the final sample size for the current study. Prior to conducting Structural Equation Modelling (SEM), Exploratory Factor Analysis (EFA) is performed to scrutinize the underlying dimensions of Financial Knowledge (FK), Financial Practice (FP) and Business Success (BS). The reliability analysis is checked via Cronbach’s alpha coefficient of the three extracted factors for the purpose of ensuring the internal consistency. Next, mediating relationship is performed using SEM to indicate the appropriateness of the measurement instruments. Findings – The results indicate that, although Financial Knowledge (FK) is positively related to the Financial Practice (FP) in Malaysian small business, but it is not directly related to the Business Success (BS). Apart from this, the Financial Practice (FP) is found assertively allied to the Business Success (BS) while Financial Practice (FP) plays the mediating roles in the Financial Knowledge (FK) towards Business Success (BS) in Malaysia. Practical implications – The current study adds value to the current level of knowledge in the existing literature. This research conveys an understanding to the entrepreneurs regarding the financial knowledge items those are more essential and play as the remedy to get the business success swiftly. Furthermore, the current study brings some implications to the policy makers and regulators as well. Originality/value – The research creates the value in Malaysian small business milieu since there is a dearth of empirical studies previously conducted highlighting the mediating relationship of financial practice between financial knowledge and business success of small business in Malaysia.